2021
DOI: 10.1002/ejp.1761
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative sleep quality and adverse pain outcomes after total hip arthroplasty

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…Congruent with results from the referenced systematic review by O'Hagan et al, we have also found that perioperative pharmacologic sleep promotion may improve postoperative pain control . Our results demonstrated a connection between poor preoperative sleep quality and adverse postoperative pain outcomes, which strengthens prior evidence of a causal relationship between sleep and pain (Bjurstrom et al, 2021). We acknowledge, however, as stated in 'Limitations and recommendations for future studies', that longitudinal objective sleep data (actigraphy and/or polysomnography) would add specificity to these findings.…”
Section: Response To: 'The Relationship Between Preoperative Sleep Qu...supporting
confidence: 83%
“…Congruent with results from the referenced systematic review by O'Hagan et al, we have also found that perioperative pharmacologic sleep promotion may improve postoperative pain control . Our results demonstrated a connection between poor preoperative sleep quality and adverse postoperative pain outcomes, which strengthens prior evidence of a causal relationship between sleep and pain (Bjurstrom et al, 2021). We acknowledge, however, as stated in 'Limitations and recommendations for future studies', that longitudinal objective sleep data (actigraphy and/or polysomnography) would add specificity to these findings.…”
Section: Response To: 'The Relationship Between Preoperative Sleep Qu...supporting
confidence: 83%
“…We note with interest the recently published observational study by Bjurström et al titled: 'Preoperative sleep quality and adverse pain outcomes after total hip arthroplasty'. The authors conclude by suggesting 'targeting sleep and achieving even modest improvements in sleep might translate into meaningful clinical improvements in pain' (Bjurström et al, 2021). To their credit, the authors are cautious while presenting this conclusion.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 96%
“…Perioperative sleep disturbance is a risk factor for the development of persistent pain after surgery ( 44 46 ). Pre-clinically, a single pre-operative exposure to REM sleep deprivation/disturbance (RSD) for 6 h has been shown to enhance mechanical hypersensitivity in female rats on day 3–4 post-surgery ( 25 ), while pre- or peri-operative RSD for 24 h or 3 days (6 h/day) increases mechanical, thermal and cold hypersensitivity in male rats for up to 9 days post paw-incision surgery ( 22 24 ) ( Table 1 ).…”
Section: The Effect Of Stress On Post-surgical Nociceptive Respondingmentioning
confidence: 99%